Odrębność postępowania kinezyterapeutycznego u pacjentów po amputacjach naczyniowych w obrębie kończyn dolnych = Separation kinesiotherapeutic proceedings in patients with vascular amputations in the lower legs - Agnieszka Radzimińska; Karolina Janowczyk; Katarzyna Strojek; Aleksander Goch; Walery Zukow (Kazimierz Wielki University, 2017)
Radzimińska Agnieszka, Janowczyk Karolina, Strojek Katarzyna, Goch Aleksander, Zukow Walery. Odrębność postępowania kinezyterapeutycznego u pacjentów po amputacjach naczyniowych w obrębie kończyn dolnych = Separation kinesiotherapeutic proceedings in patients with vascular amputations in the lower legs. Journal of Education, Health and Sport. 2016;6(11):11-23. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.163457 http://ojs.ukw.edu.pl/index.php/johs/article/view/3958         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 26.10.2016.       Odrębność postępowania kinezyterapeutycznego u pacjentów po amputacjach naczyniowych w obrębie kończyn dolnych Separation kinesiotherapeutic proceedings in patients with vascular amputations in the lower legs   Agnieszka Radzimińska¹, Karolina Janowczyk¹, Katarzyna Strojek¹, Aleksander Goch2, Walery Zukow3  1.      Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy, Katedra Fizjoterapii, Zakład Podstaw Fizjoterapii, Bydgoszcz, Polska 2.      Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy, Katedra Fizjoterapii, Bydgoszcz, Polska 3.      Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Bydgoszcz, Polska     Słowa kluczowe: kinezyterapia, pacjent, amputacje naczyniowe, kończyny dolne. Key words: kinesiotherapy, patient, vascular amputations, lower limbs.   Streszczenie             Amputacja, czyli operacyjne odjęcie kończyny lub jej części, jest jednym z najstarszych zabiegów w historii medycyny. Obecnie, przeważająca część amputacji (ok. 80-90%) odbywa się z powodu powikłań chorób naczyniowych. W zależności od obszaru dotkniętego zmianami tkanek oraz rozległości tego procesu, chirurg podejmuje decyzję o poziomie odjęcia kończyny. Po amputacji istnieje ryzyko wystąpienia wielu powikłań, m.in.: zakażenie beztlenowcami, rozejście się rany, martwica skóry, obrzęk oraz przykurcze. W przypadku amputacji planowych ćwiczenia powinno się rozpocząć jeszcze przed operacją, aby przygotować organizm pacjenta do nadchodzących zmian. Kinezyterapia ma na celu wzmocnienie kończyn, zarówno tej, której część zostanie usunięta, a także zdrowej kończyn, która będzie  musiała  przejąć ciężar ciała do czasu zaprotezowania oraz nauczenia pacjenta posługiwania się protezą. Zaleca się ćwiczenia czynne oraz czynne z oporem kończyn górnych, dolnych oraz tułowia, a także ćwiczenia oddechowe. Niezwykle istotne jest przygotowanie psychiczne pacjenta do amputacji poprzez ukazania  możliwości funkcjonowania jak przed operacją. Jednym z jej elementów jest profilaktyka przeciwzakrzepowa, w której skład wchodzą: wysokie ułożenie kończyny, manualny drenaż limfatyczny oraz ćwiczenia bierne i czynne,  pobudzające pompę mięśniową. Przykurcze są jednym z najczęstszych problemów po amputacji, które wpływają negatywnie na proces protezowania. Działaniem zapobiegającym powstaniu przykurczy są pozycje ułożeniowe, które nie powodują patologicznego ustawienia kończyny. Innymi zabiegami, które wykonuje  fizjoterapeuta, jest  hartowanie kikuta oraz jego bandażowanie. Powyższe działania mają na celu uzyskanie prawidłowo ukształtowanego kikuta, gdyż tylko taki kikut można łatwo zaopatrzyć.   Summary Amputation or subtracting operating limb or part thereof, is a the oldest treatments in the history of medicine. Currently, most of the amputation (Approx. 80-90%) takes place due to complications of vascular diseases. Depending on the area affected by changes in the tissues and the extent of this process, the surgeon decides on the level of subtracting limb. After the amputation, there is the risk of many complications, m.in.: anaerobic infection, wound dehiscence, necrosis of the skin, swelling and contracture. In the case of amputation planned exercises should be started before surgery to prepare your body for the upcoming changes. Kinesiotherapy is intended to strengthen the limbs, both of which part will be removed, and the healthy limbs, which will have to take the weight of the body until moment of prosthesis and teach the patient to use the prosthesis. It is recommended that active exercises and active with the resistance of the upper limbs, lower limbs and trunk, and breathing exercises. It is extremely important mental preparation of the patient for amputation through the show the ability to function as before the operation. One of its elements is a prophylaxis, which includes: a high arrangement of limbs, manual lymphatic drainage and exercises passive and active, stimulating muscle pump. Contractures are one of the most common problems after the amputation, which negatively affect the process of prosthesis. Action to prevent the formation of contractures are positional positions that do not cause pathological settings limbs. Other treatments that performs a physical therapist, a hardening of the stump and its bandage. These activities are aimed at obtaining properly shaped stump, since only the stump can easily obtain.